Multinational repositories (MNRs) highlight the need for transnational information management in geological disposal - Chapman, Neil; McCombie, Charles (Frontiers in Nuclear Engineering, 2023)
Multinational geological repositories (MNRs) will inevitably be features of the international radioactive waste management landscape in future decades. They will involve more complex requirements for long-term information management than national deep geological repositories (DGRs), but the considerations involved in managing these requirements also point to wider needs for transnational information management for any country with a national DGR. This article looks at what information needs to be propagated into the future for both DGRs and MNRs, and for how long. It is argued that the critical requirements are quite limited and are readily achievable, with the most important period being the coming few hundred years. The transience of organisations and national boundaries, issues being addressed for MNRs, also affect any national programme, but are generally overlooked. It is concluded that there is a need to move towards international oversight of all geological disposal facilities, including a common system of regulations and information archiving, and that providing these is a potential role for the IAEA.